Policy Options to Remove Export Barriers Encountered by Indonesian SMEs - Mohamad Dian Revindo; Sri Mulyani Indrawati; Natanael Waraney Gerald Massie (Jurnal Ekonomi Indonesia, 2019)
Indonesian SMEs are less able to take advantage of free trade and globalization than their large counterparts, contributing only a small share of non-oil and gas exports. This study investigates the export barriers faced by SMEs. Primary data was obtained from survey questionnaires to SMEs in seven provinces in Java, Madura and Bali regions and central government agencies whose policies are related to SMEs and/or international trade. The survey yielded 533 usable responses, including 271 exporting SMEs, 226 non-exporting SMEs and 36 central government agencies. The findings show that the effectiveness of export assistance programs vary across types of assistance and levels of government. Further, policymakers and SMEs had different perceptions on the severities of each type of export barrier. The practical implications of the findings are provided.